Regional Social Development Gap and Regional Coordinated Development Based on Mixed-Methods Research: Evidence From China - Liu, Weiwei; Liu, Zhiwei; Wang, Lian; Liu, Haiming; Wang, Yan (Frontiers in Psychology, 2022)
Due to the continuous acceleration of the global urbanization process, the unbalanced development of regional cities has become an unavoidable reality under the rapid economic and social development of China. The unbalanced social development will affect the coordinated and sustainable economic development, regional ethnic unity and political and social stability. This research uses data from 2011-2015 period、2016-2020 period and various special development plans of 35 large and medium cities, combines qualitative analysis and quantitative analysis, establishes a comprehensive evaluation model and conducts cluster analysis, using standard deviation, The coefficient of variation aims to measure and study whether the gap in China's regional social development has continued to widen over the past decade. This study found that: 1) From the overall national perspective, there are obvious differences in the level of social development in the development plans of 35 large and medium-sized cities. The social development level of each large and medium-sized city has been improved to a certain extent, and the social development gap between cities has also been reduced to a certain extent. 2) From the 2011-2015 period to the 2016-2020 period, the social development gap between the three regions of my country's eastern, central and western regions has declined. 3) The trend of social development disparity within the three major regions of the eastern, central and western regions is not the same. The internal social development gap in the eastern region shows a downward trend, while the internal social development gap in the central and western regions shows an upward trend. This study provides a valuable reference for rapidly urbanizing developing countries in the process of globalization.